Post-hoc analysis on the R&D capabilities of chemical and metallurgical manufacturing companies - Anuar, Herman Shah; Mohamed Udin, Zulkifli; Mohd Nawi, Mohd Nasrun (ESRSA Publications Pct. Ltd., 2013)
The purpose of this paper is to evaluate how internal R&D, external R&D, and patenting affects the behavior of foreign, local, and joint-venture companies operating in manufacturing companies in Malaysia.Different types of manufacturing companies may have different approach in applying their R&D capabilities and patenting activity.The construct of this paper is based on the post-hoc analysis in evaluating how internal R&D, external R&D, and patenting affects the behavior of foreign, local, and joint-venture companies operating in manufacturing companies.This research was conducted using survey questionnaires, 124 companies in chemical and metallurgical manufacturing companies participated in this survey.It was indicated that these three companies behave differently when dealing with internal R&D, external R&D, and patenting.It can be inferred that these three types of companies have a different perspective on applying internal R&D, external R&D, and patenting which is based on their different business strategic direction. It is suggested that in the near future, researchers should concentrate and other types of manufacturing companies or they can involve more sample size in getting better generalization on the behavior of these companies.